Indications for extraction of permanent maxillary canines – a literature review - Baszak, Jakub; Sobieszańska, Anna; Dunin-Wilczyńska, Izabella (Forum Ortodontyczne / Orthodontic Forum, 2018)
Orthodontic movement of a maxillary canine into the dental arch may be a therapeutic challenge, and it is necessary to analyse a case in detail and to evaluate therapeutic methods, including a difficult decision of tooth extraction in all cases. Aim. The paper aims to discuss orthodontic indications for maxillary canine extraction based on available literature. Material and methods. The PubMed database and the following key words were used for studies: canine impaction, maxillary impacted canine and canine extraction. Literature was supplemented with publications from reviewed journals not included in the PubMed database. 50 papers were selected from the literature list. Results, review and discussion. A decision to extract a maxillary canine should be made based on a detailed clinical examination and analysis of orthodontic records, including photographs, diagnostic models and radiological scans. CBCT imaging test should be performed as standard before treatment in case of impaired tooth eruption. Factors that should be especially considered include: tooth anatomy, periodontal status, position in the bone, occlusion, condition of the adjacent teeth and any pathological processes in the tooth vicinity. Before making a therapeutic decision a patient should be informed about available therapeutic options according to current medical knowledge, as well as about advantages and disadvantages of each of them. Summary. Factors favouring extraction of impacted canines or canines with impaired eruption include: unfavourable position (a horizontal position of a tooth in the bone, position in the zone IV and V according to Kurol, large distance from the edge of the alveolar process), anatomical abnormality (root angulation, external or internal resorption), root ankylosis, patient’s age above 30 years and good occlusion without a canine in the dental arch with the need to extract a premolar for its movement into the dental arch. (Baszak J, Sobieszczańska A, Dunin-Wilczyńska I. Indications for extraction of permanent maxillary canines – a literature review. Orthod Forum 2018; 14: 130-42).